The Influence of Leadership, Non-Physical Work Environment, and Occupational Health and Safety on the Work Productivity of Technician Employees PT. MADAS Elektrikal Kontraktor Tembilahan - Anggraini, Wenty; Hendriani, Susi; Nuryanti, Nuryanti (CV. Rayyan Dwi Bharata, 2024)
This research was conducted with the aim of determining the direct influence of leadership variables, non-physical work environment, and occupational health and safety on the work productivity of technician employees PT. MADAS Elektrikal Kontraktor Tembilahan. This type of research uses quantitative research. The population in this study was all 42 technician employees. This research used technician employees of PT. MADAS Elektrikal Kontraktor Tembilahan as research object. The sampling method used a saturated sample, namely 42 respondents. The analytical method used in processing this research data is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and coefficient of determination using a significance level of 0.05. The data processing for this research uses the help of SPSS 23 software. Based on the results of the research conducted, it shows that leadership variables, non-physical work environment, and occupational health and safety have a positive and significant effect on the work productivity of technician employees PT. MADAS Elektrikal Kontraktor Tembilahan.